2021
DOI: 10.3390/polym13010162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Processing on Flow Properties and Stability of Thickened Fluid Matrices Formulated by Tapioca Starch, Hydroxyl Distarch Phosphate (E-1442), and Xanthan Gum Associating Dysphagia-Friendly Potential

Abstract: The flow behavior of the administrated fluid matrices demands careful assessments for stability when consumed by individuals with dysphagia. In the present study, we incorporated tapioca starch (TS), hydroxypropyl distarch phosphate (HDP), and xanthan gum (XG) as thickeners into different nectars (300 ± 20 mPa.s) undergoing thermal processing and evaluated their stability. The thickened nectars presented better water holding and oil binding capacities at 25 °C than 4 °C, and the nectars with TS provided the be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 57 publications
3
16
0
Order By: Relevance
“…Overall, the contrasting rheological features noticed between AP and XG hydrocolloids suggest that they may play complementary roles in producing food products for various applications with DFMs. The apparent viscosity can be measured by a rotary viscometer with recommend shear rate of 50 s −1 ; it was previously reported that apparent viscosity of a 0.694% XG contained matrix is 307.1 ± 936 mPa•s [23], which is comparable to our XG0.5 data of 238.9 ± 5.61 mPa•s, as well as our AP2 data of 238.2 ± 4.82 mPa•s.…”
Section: Rheological Properties Of Xg At Various Concentrationssupporting
confidence: 90%
See 4 more Smart Citations
“…Overall, the contrasting rheological features noticed between AP and XG hydrocolloids suggest that they may play complementary roles in producing food products for various applications with DFMs. The apparent viscosity can be measured by a rotary viscometer with recommend shear rate of 50 s −1 ; it was previously reported that apparent viscosity of a 0.694% XG contained matrix is 307.1 ± 936 mPa•s [23], which is comparable to our XG0.5 data of 238.9 ± 5.61 mPa•s, as well as our AP2 data of 238.2 ± 4.82 mPa•s.…”
Section: Rheological Properties Of Xg At Various Concentrationssupporting
confidence: 90%
“…The results of the frequency sweep shown in Figure 2d further indicate that, with increased XG concentration, the hydrocolloid may be converted from a critical gel (G' ≈ G") to a strong gel (G' >> G"), exhibiting little dependence on angular frequency. It was recently documented that for a 0.694%XG contained matrix of distilled water base that underwent a 6 min thermal process at 80 • C; the G' and G" remained consistent at the approximate range of 10 Pa [23], which is comparable to the present work of XG 0.5. They also present shear moduli of 4.17% hydroxyl distarch phosphate (a resistance starch approved for use in the European Union with the listed number of E1442) in a distilled water based hydrocolloid that underwent a 3-min thermal process at 80 • C; both moduli are slightly higher than those of 0.694% XG contained matrix with a G' range less than 200 Pa.…”
Section: Rheological Properties Of Xg At Various Concentrationssupporting
confidence: 87%
See 3 more Smart Citations